2001
DOI: 10.1017/s1355838201001741
|View full text |Cite
|
Sign up to set email alerts
|

A tertiary structure model of the internal ribosome entry site (IRES) for methionine-independent initiation of translation

Abstract: Cricket paralysis-like viruses have a dicistronic positive-strand RNA genome. These viruses produce capsid proteins through internal ribosome entry site (IRES)-mediated translation. The IRES element of one of these viruses, Plautia stali intestine virus (PSIV), forms a pseudoknot immediately upstream from the capsid coding sequence, and initiates translation from other than methionine. Previously, we estimated that the IRES element of PSIV consists of seven stem-loops using the program MFOLD; however, experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
135
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 24 publications
7
135
0
Order By: Relevance
“…Hence, these studies also indicated that SL1 is not required for 80S preinitiation complex formation but that intact SL2 is required. These results are similar to those reported from in vitro studies with RhPV and PSIV (Domier et al, 2000;Kanamori & Nakashima, 2001). From these studies we conclude that the RhPV IG IRES initiated translation with efficiencies comparable to that of the 59 IRES and that the IG IRES was not dependent on the presence of the 59 IRES.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Hence, these studies also indicated that SL1 is not required for 80S preinitiation complex formation but that intact SL2 is required. These results are similar to those reported from in vitro studies with RhPV and PSIV (Domier et al, 2000;Kanamori & Nakashima, 2001). From these studies we conclude that the RhPV IG IRES initiated translation with efficiencies comparable to that of the 59 IRES and that the IG IRES was not dependent on the presence of the 59 IRES.…”
supporting
confidence: 91%
“…These results showed that the RhPV IG IRES directed internal initiation in Sf9 cells. In addition, it confirmed the in vitro observations with RhPV and PSIV that showed that the 39 pseudoknot was required for IRES activity (Domier et al, 2000;Kanamori & Nakashima, 2001).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Molecular structure of the CrPV IRES RNA At the present resolution, it is not possible to derive directly the identity of the helical RNA elements or their directionality, but the established secondary structure of the CrPV IRES [16][17][18] indicates the presence of three pseudoknots (PKI, PKII and PKIII) and establishes the length and connectivity of the helical elements (Fig. 2c).…”
Section: Cryo-em Reconstruction Of the Crpv Ires-80s Complexmentioning
confidence: 94%